2017
DOI: 10.1111/jgs.14771
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Posttraumatic Stress Symptoms and Association with Fear of Falling After Hip Fracture

Abstract: Background Common fall-related injuries including hip fracture may put elderly individuals at risk for the development of posttraumatic stress disorder (PTSD). Similar to Fear of Falling (FoF), PTSD could negatively impact physical recovery due to behavioral avoidance. Methods We examined rates of partial and full posttraumatic stress disorder (pPTSD and fPTSD) and compared them to rates of FoF in 456 individuals age 60 and older who were admitted as inpatients for surgical hip fracture repair after a fall. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 46 publications
0
12
0
Order By: Relevance
“…65 Our study advances the field demonstrating the increased risk of falls requiring hospitalization in older adults with bipolar disorder. For stress-related disorders, although previous research has suggested that some cases could arise as a consequence of both a fall and hip fracture and lead to worse outcomes, 66 previous research has also reported that older adults with depressive symptoms, that is, a potentially related group, have an increased risk of hip osteoporosis, 30 self-report falls, 38 and fractures. 67 Our data indicate that people with clinical depression specifically have a 2.2 and 3.9 increased risk of hospitalized falls and hip fractures, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…65 Our study advances the field demonstrating the increased risk of falls requiring hospitalization in older adults with bipolar disorder. For stress-related disorders, although previous research has suggested that some cases could arise as a consequence of both a fall and hip fracture and lead to worse outcomes, 66 previous research has also reported that older adults with depressive symptoms, that is, a potentially related group, have an increased risk of hip osteoporosis, 30 self-report falls, 38 and fractures. 67 Our data indicate that people with clinical depression specifically have a 2.2 and 3.9 increased risk of hospitalized falls and hip fractures, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Of the 152 patients in this study, 72.4% were concerned about postoperative recovery, rehabilitation, and re-fracture; 63.2% were concerned about recovery of walking; and 52.6% were concerned about return to work and daily life activities. Kornfield, et al 19 reported that anxiety about re-fracture is highly associated with post-traumatic stress disorder and that hip fracture in older adults causes great psychological and physical stress and increased mortality and morbidity. In the future, based on the results of this and other studies, it is necessary to establish protocols for preventing re-fracture and interventions to relieve the stress caused by hip fracture in the elderly.…”
Section: Discussionmentioning
confidence: 99%
“…This may lead to depression and the literature in this area is rapidly expanding ( Cristancho et al 2016 ). It may also result in variants of post-traumatic stress disorder, albeit infrequently ( Kornfield et al 2017 , Salkeld et al 2000 ).…”
Section: Postoperative Considerationsmentioning
confidence: 99%